APPLICATION OF WEB -BASED LEARNING MEDIA TO IMPROVE SANTRI COMMUNICATION SKILLS - Zainal Abidin; Syaiful Bahri (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to evaluate the application of web-based learning media in improving Santri's communication skills. This study focuses on the effectiveness of using web technology in improving students' ability to communicate. The research method uses an experimental approach, involving a control group and an experimental group. identified as research subjects. The use of web platforms for learning is used in a structured manner and integrated into the curriculum to help students develop their communication skills. The results showed a significant improvement in the communication skills of students involved in web-based learning compared to the control group. Quantitative and qualitative data analysis provides a clear picture of the progress achieved by students through the use of web-based learning media. The findings from this research indicate that web-based learning media is effective in improving the communication skills of class VII students. The implications of this research highlight the importance of integrating web technology in an educational context to strengthen students' communication skills. This research provides a basis for further development in the application of web-based learning media to improve the communication skills of students, not only students, but also in the broader educational context Keywords : Approach Ethno -STEM, Skills Think Critical , Student Interest